Convergence of the quantum Navier–Stokes–Poisson equations to the incompressible Euler equations for general initial data. (June 2015) - Yang, Jianwei; Ju, Qiangchang
Abstract: In this paper, we are concerned with the rigorous proof of the convergence of the quantum Navier–Stokes-Poisson system to the incompressible Euler equations via the combined quasi-neutral, vanishing damping coefficient and inviscid limits in the three-dimensional torus for general initial data. Furthermore, the convergence rates are obtained.